Generic Spaces in Middleton's The Triumphs of Truth (1613) and Michaelmas Term (1607). Issue 88 (October 2015) - Anderson, Susan
This article compares Middleton's The Triumphs of Truth (1613) and Michaelmas Term (printed 1607), in order to examine the representation of places of display in different kinds of space, and to determine some of the ways in which genres of performance and writing influence the way that space is defined. In particular, it examines the status of the shop as a type of space. It offers the concept of situation as a way of accounting for the interrelationships between text, time, place and space, and the structuring of habit and perception within those contexts.